2006
DOI: 10.1007/s11095-006-9051-0
|View full text |Cite
|
Sign up to set email alerts
|

Solute Crystallization in Frozen Systems–Use of Synchrotron Radiation to Improve Sensitivity

Abstract: By using synchrotron radiation, solute crystallization was detected with substantially increased sensitivity, making the technique useful for freeze-drying cycles of practical and commercial importance. Since numerous peaks of the crystalline solute appeared, the technique has potential utility in complex, multi-component systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Pronounced pH shift, up to 3 units, were observed when the initial buffer concentrations were ≥50 mM (15,16). In our previous report, using synchrotron X-ray diffractometry (SXRD), we have demonstrated the effect of initial solute concentration (ranging from 1 to 100 mM) on the selective crystallization of DHPD (19). Gomez et al developed an elegant method to monitor pH changes at temperatures ≥ −20°C by using a low temperature electrode (15,16).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Pronounced pH shift, up to 3 units, were observed when the initial buffer concentrations were ≥50 mM (15,16). In our previous report, using synchrotron X-ray diffractometry (SXRD), we have demonstrated the effect of initial solute concentration (ranging from 1 to 100 mM) on the selective crystallization of DHPD (19). Gomez et al developed an elegant method to monitor pH changes at temperatures ≥ −20°C by using a low temperature electrode (15,16).…”
Section: Introductionmentioning
confidence: 98%
“…Pyne et al demonstrated a complex interplay between the amorphous and crystalline phases in the ternary system composed of mannitol, glycine and sodium phosphate (14). The crystallization of buffer salts (e.g., in the case of sodium phosphate buffer) from the freeze-concentrate is not desired due to the potential for significant pH shifts that can affect the stability of API (7,9,(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 For example, heat-induced crystallization of a component salt in some buffer systems (e.g., sodium phosphate) significantly shift pH of the freeze-concentrated solutions and dried solids, and thus alters the stability of colyophilized proteins. 26,27 Reported phase separation of freeze-dried trehalose and dextran upon exposure to the higher temperature and humidity 28 suggested chances for similar component miscibility changes during the heat treatment of frozen solutions.…”
Section: Introductionmentioning
confidence: 99%
“…173 In another study, synchrotron X-ray diffractometry has been used to detect solute crystallization in frozen sodium phosphate buffer solutions. 174 In this work, it was established that the use of synchrotron diffraction yielded substantially increased sensitivity, and that the technique was particularly useful in complex, multi-component systems.…”
Section: Phase Transformations Of Polymorphs and Solvatomorphsmentioning
confidence: 99%